THE EFFECT OF SOCIAL BEHAVIOR ON NEW NORMAL LEARNING IN STUDENTS - Laura Fitriana; Rantika Fitri; Adelia Mardianti; M. Najarudin Rizki; Dessy Meteorina (CV. Doki Course and Training, 2023)
Students are able to build their self-confidence and motivation to learn either independently or through observing their social environment. The changes in learning atmosphere and condition after the Covid-19 pandemic are interesting to be studied and becomes an assessment of learning. The social activities of the society are getting back to normal, including learning. Education institutions started to re-arrange their curriculum to get back to the pre-pandemic condition. In this case, we are going to discuss whether the existing social behavior of students can be affected and ease the learning process in the new normal era and at the same time to look at the benefits brought by the new learning system with the Online Learning Technique. The purpose of this research is to look at how the social behavior of psychology faculty students in adapting to the new normal learning era. This research used quantitative research method with data collection method using 10 items of Social Behavior and 10 items of New Normal Learning. The data were analyzed using simple regression with the results showing the value (xry) = 0,445 with p = 0,001 (p <0.05) which means there is a positive correlation between the X and Y variables of 22.1%.